Pengembangan Website di Sekolah SMK Advent Batam - Sama, Hendi; Fernando, Ricky (Journal of Information System and Technology (JOINT), 2024)
Digital technology is a discovery that continues to evolve along with the development of the world. Digital technology can be utilized for various purposes, such as supporting the teaching and learning process and accessing information more easily. One of the digital media that can be used to support schools is a profile website. The presence of a profile website can have a significant impact on users, such as prospective students and parents, as well as support school promotion and communication. This project aims to develop a profile website for SMK Advent Batam to provide information about the school's facilities, expertise programs, and activities. Data collection was carried out through literature studies and interviews with the principal. The result of this project is a responsive website that supports SMK Advent Batam's online visibility and effective communication.